Ziemia Lubuska w polsko-niemieckim dialogu - rekonesans i zarys perspektyw = The Lubuskie Region in Polish-German dialogue - current insights and future perspectives - Bąkiewicz, Marta Jadwiga (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article discusses the dimensions of Polish-German dialogue (scientific, literary, cultural) in relation to the Lubuskie Region. It is based on an assumption that this region plays an important role in the dialogue between cultures.
Keywords: region; Ziemia Lubuska; polsko-niemiecki dialog; kontakty kulturalno-literackie; Lubuskie Region; Polish-German dialogue; cultural and literary contacts